Expression of epithelial-mesenchymal transition-related genes in prostate tumours - Gerashchenko, G.V.; Mankovska, O.S.; Dmitriev, A.A.; Mevs, L.V.; Rosenberg, E.E.; Pikul, M.V.; Marynychenko, M.V.; Gryzodub, O.P.; Stakhovsky, E.O.; Kashuba, V.I. (Вiopolymers and Cell, 2017)
Aim. To detect expression of EMT-related genes in prostate tumor samples and analyze a possible correlation between gene expression level and clinical characteristics of prostate cancer in different groups. Methods. Expression of 19 genes was analyzed in 37 frozen samples of prostate cancer tissues at different tumor stages and Gleason scores, 37 paired conventionally normal prostate tissues and 20 samples of prostate adenomas, using quantitative PCR. Results. We have found that nine genes were expressed differently in benign and malignant prostate tumors, namely AR (1 isof), AR (2 isof), PTEN, VIM, MMP9, KRT18, PCA3, HOTAIR and SCHLAP1. When different tumor stages were compared, we could identify six differentially expressed genes: KRT18, MMP9, VIM, PCA3, HOTAIR and SCHLAP1; when samples of tumors with different Gleason score were compared, we found that eight genes were expressed differently: AR (1isof), CDH1, KRT18, MMP9, OCLN, PCA3, HOTAIR and SCHLAP1. The data had a high level of heterogeneity pottentially due to various molecular subtypes of prostate cancer, i.e. a luminal subtype with ahigh expression of CDH1, OCLN, AR(1 isof), KRT18, NKX3-1 and PSA; the stem-like subtype with a high expression of mesenchymal markers CDH2, FN1 and VIM and low expression of the epithelial markers. It is noteworthy that lncRNAs were specifically expressed in these two molecular subtypes. Conclusions. EMT-related genes were differentially expressed in benign and malignant prostate tumors. High heterogeneity of expression levels, especially in adenocarcinoma groups, might suggest the existence of at least two different molecular subtypes, luminal and stem-like. Further experiments are necessary for specification of the molecular subtypes of prostate adenocarcinoma. Мета. Встановити відносну експресію у ЕМП-пов’язаних генах у зразках пухлин передміхурової залози та проаналізувати можливу кореляцію та зв'язок між рівнем експресії генів у різних групах пухлин та клінічними характеристиками раку передміхурової залози. Методи. Відносні рівні експресії 19 генів у 37 заморожених зразках тканин раку передміхурової залози з різними показниками Глісона та стадіями пухлин, 37 парних умовно-нормальних зразків тканини передміхурової залози та 20 зразків аденоми простати було детектовано кількісною ПЛР (QPCR). Результати. Було виявлено 9 диференційно експресованих генів у доброякісних та злоякісних пухлинах простати: (AR (1 isof), AR (2 isof), PTEN, VIM, MMP9, KRT18, PCA3, HOTAIR, SCHLAP1). На різних стадіях раку виявлено 6 диференційно експресованих генів (KRT18, MMP9, VIM, PCA3, HOTAIR, SCHLAP1), а за різними оцінками Глісона виявлено 8 диференційно експресованих генів (AR (1 isof), CDH1, KRT18, MMP9, OCLN, PCA3, HOTAIR, SCHLAP1). Спостерігався значний рівень дисперсії даних. Це можна пояснити наявністю різних молекулярних підтипів раку передміхурової залози: люмінальний підтип (висока експресія CDH1, OCLN, AR (1 isof), KRT18, NKX3-1, PSA) і стовбуровий (базальний) підтип (висока експресія мезенхимальних маркерів CDH2, FN1, VIM і низька експресія епітеліальних маркерів). Досліджені некодуючі РНК були специфічно експресованіі у двох молекулярних підтипах. Висновки. пов'язані з ЕМП гени диференційно експресуються у доброякісних та злоякісних пухлинах передміхурової залози. Висока дисперсія даних експресії, особливо в групах аденокарциноми, може бути свідченням принаймні двох різних молекулярних підтипів: люмінального і стовбурового (базального). Нами продемонструвано, що умовно-нормальні тканини передміхурової залози не є адекватним контролем. Для уточнення молекулярних підтипів аденокарциноми передміхурової залози необхідні додаткові дослідження. Цель. Установить уровни относительной экспрессии генов, связанных с ЭМП, в образцах опухолей предстательной железы и проанализировать возможную корреляцию и взаимосвязь между уровнем экспрессии генов в разных группах опухолей и клиническими характеристиками рака простаты. Методы. Относительные уровни экспрессии 19 генов в 37 замороженных образцах тканей рака предстательной железы с разными показателями Глисона и стадиями рака, 37 парных образцов условно-нормальной ткани простаты и 20 образцов аденомы предстательной железы были проанализированы с помощью количественной ПЦР (QPCR). Результаты. Было выявлено 9 дифференциально экспрессированных генов в доброкачественных и злокачественных опухолях предстательной железы: (AR (1 isof), AR (2 isof), PTEN, VIM, MMP9, KRT18, PCA3, HOTAIR, SCHLAP1). На разных стадиях рака были идентифицированы 6 дифференциально экспрессированных генов (KRT18, MMP9, VIM, PCA3, HOTAIR, SCHLAP1), тогда как с разными показателями по шкале Глисона было найдено 8 дифференциально экспрессированных генов (AR (1isof), CDH1, KRT18, MMP9, OCLN, PCA3, HOTAIR, SCHLAP1). Наблюдалась очень высокая дисперсия данных. Это может быть объяснено наличием различных молекулярных подтипов рака предстательной железы: люминального подтипа (высокая экспрессия CDH1, OCLN, AR (1 изоф), KRT18, NKX3-1, PSA) и стволового (базального) подтипа (высокая экспрессия мезенхимальных маркеров CDH2, FN1, VIM и низкая экспрессия эпителиальных маркеров). Исследованные некодирующие РНК специфически экспрессировались в двух молекулярных подтипах. Выводы. Гены, связанные с ЭМП, были дифференциально экспрессированы в доброкачественных и злокачественных опухолях предстательной железы. Высокая дисперсия данных экспрессии, особенно в группе аденокарцином, может свидетельствовать, по меньшей мере, о двух разных молекулярных подтипах: люминальном и базальном. Мы продемонстрировали, что условно-нормальные ткани простаты не являются адекватным контролем. Для уточнения молекулярных подтипов аденокарциномы предстательной железы необходимы дополнительные исследования.